2010
DOI: 10.1111/j.1471-6712.2009.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Iranian diabetic adolescent girls’ quality of life: perspectives on barriers

Abstract: As most paediatric teams are multidisciplinary, sharing the information regarding QoL barriers as part of ongoing clinical care is crucial and should help to tailor care to the needs of the adolescent with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Both groups said most people outside the family did not remember, know about, or care that participants had T1DM. This is consistent with other findings suggesting this group, including teachers, may not remember receiving information or know much about T1DM (Wennick et al 2009, Maslakpak et al 2010. Both groups also denied being teased or experiencing prejudice from friends, but rather saw peers as helpful and supportive, similar to other studies (Faulkner 2003, Hall-Lande et al 2007, Karlsson et al 2008.…”
Section: Discussion Similaritiessupporting
confidence: 90%
See 1 more Smart Citation
“…Both groups said most people outside the family did not remember, know about, or care that participants had T1DM. This is consistent with other findings suggesting this group, including teachers, may not remember receiving information or know much about T1DM (Wennick et al 2009, Maslakpak et al 2010. Both groups also denied being teased or experiencing prejudice from friends, but rather saw peers as helpful and supportive, similar to other studies (Faulkner 2003, Hall-Lande et al 2007, Karlsson et al 2008.…”
Section: Discussion Similaritiessupporting
confidence: 90%
“…, Maslakpak et al . ). Both groups also denied being teased or experiencing prejudice from friends, but rather saw peers as helpful and supportive, similar to other studies (Faulkner , Hall‐Lande et al .…”
Section: Discussionmentioning
confidence: 97%
“…As challenges for children and youth with T1DM affect their quality of life (Maslakpak et al . ), it is important to learn more about their experiences so appropriate interventions can be developed to help them cope, adjust to their situation, improve their quality of life and encourage more understanding and appropriate relationships within the family (Court et al . , Northam et al .…”
Section: Introductionmentioning
confidence: 99%
“…The QoL of diabetic adolescents is associated with several factors, so it is the focus of several studies [12][13][14][15][16]18,22,23 . Adolescence is a stage characterized by conflicts, autonomy, immediacy, issues regarding the conduct of parents and other adults and the need to be accepted by the group, which probably hinders diabetic adolescents' coping with the disease and compromises their condition.…”
Section: Factors That Interfere In the Qol Of Diabetic Adolescentsmentioning
confidence: 99%
“…In Iran, a survey 18 carried out with female diabetic adolescents sought to understand the barri-ers that interfere in the QoL of these adolescents. Among them, authors identified social barriers related to family issues, the social perspective on diabetes and school problems; and personal issues that involve negative feelings about treatment and care, the negative effects of diabetes and uncertainty about the future.…”
Section: Factors That Interfere In the Qol Of Diabetic Adolescentsmentioning
confidence: 99%